What Determines Firms' Decisions to Formalize? Empirical Evidence from Rural Indonesia - Neil McCulloch; Günther G. Schulze; Janina Voss (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
In this paper we analyze the decision of small and micro firms to formalize, i.e. to obtain business and other licenses in rural Indonesia. We use the rural investment climate survey (RICS) that comprises around 2500 non-farm rural enterprises in six Indonesian districts and analyze in an IV approach the effect of formalization on tax payments, corruption, access to credit and revenue. We take firm heterogeneity into account and show how the effect of formalization depends on firm characteristics such as firm size, education and ethnicity of the owner. We identify firm and owner characteristics that make formalization more likely.
Keywords: O17; O18; 330; Formalization; rural development; rural investment climate